Negatywny wpływ dotacji unijnych na postęp techniczny i gospodarkę Polski - Szafrański, Grzegorz (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The main goal of the article is to prove a negative causality between European funds and condition of Polish economy. The author does not intend to convince the readers to admit the validity of the represented opinion, but would like to signal the possibility of occurence of adverse consequences. Arguments are put in the medium or long term horizon. Among the negative consequences for the economy can be listed: the ineffectiveness of enterprises, too extensive bureaucracy, a waste of production factors, disturbed competition, too complicated legislation rules and the possibility of corruption and fraud.
Keywords: dotacje unijne; postęp techniczny; gospodarka; Polska